2020
DOI: 10.37511/tesis.v15n2a10
|View full text |Cite
|
Sign up to set email alerts
|

Desempeño psicométrico del Índice de Bienestar General WHO-5 en adolescentes escolarizados

Abstract: Antecedentes. El Índice de Bienestar (WHO-5) es un instrumento para medir bienestar general o síntomas depresivos en diferentes contextos y poblaciones. No obstante, el desempeño psicométrico de los instrumentos necesita revisión periódica. Objetivo. Revisar algunos indicadores del desempeño psicométrico del WHO-5, dimensionalidad y consistencia interna, en adolescentes escolarizados de Santa Marta, Colombia. Se diseñó un estudio metodológico en el que participaron 1.462 estudiantes de décimo y undécimo grado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
1
0
3
Order By: Relevance
“…The validity evidence based on the internal structure were obtained through the CFA, the results of which show appropriate fit indices for the unidimensional model, that is, the WHO-5 items translated into Collao Quechua made up appropriate indicators to measure subjective well-being as the only latent characteristic. This confirms what previous studies have found at national [ 19 ] and international [ 20 , 21 , [28] , [29] , [30] ] level that it is consistent with the original version designed by the World Health Organization [ 31 ] as a single dimension instrument considering five indicators to measure well-being in primary assistance. Additionally, taking into account the study where [ 19 ] suggest the correlation of error in items 1 and 4, whereas the research of [ 29 ] suggests the correlation of error in items 3 and 4, the modification indexes were analyzed, and it was found that it was not necessary to model the correlation among the residuals of the items translated into Collao Quechua.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The validity evidence based on the internal structure were obtained through the CFA, the results of which show appropriate fit indices for the unidimensional model, that is, the WHO-5 items translated into Collao Quechua made up appropriate indicators to measure subjective well-being as the only latent characteristic. This confirms what previous studies have found at national [ 19 ] and international [ 20 , 21 , [28] , [29] , [30] ] level that it is consistent with the original version designed by the World Health Organization [ 31 ] as a single dimension instrument considering five indicators to measure well-being in primary assistance. Additionally, taking into account the study where [ 19 ] suggest the correlation of error in items 1 and 4, whereas the research of [ 29 ] suggests the correlation of error in items 3 and 4, the modification indexes were analyzed, and it was found that it was not necessary to model the correlation among the residuals of the items translated into Collao Quechua.…”
Section: Discussionsupporting
confidence: 91%
“…Today, there are short versions (WHO-5) that have been proved to be valid and reliable in countries like Peru [ 19 ], Colombia [ 20 ], and Argentina [ 21 ], thereby becoming a good alternative due to its psychometric performance and ease of application as a 5-item scale. Therefore, this study aimed to translate and validate the WHO-5 General Well-being Index into the Collao variant of the Quechua native language spoken in Puno, Peru.…”
Section: Introductionmentioning
confidence: 99%
“…Al concluir estos procedimientos, se realizaron algunos puntos de corte (Tabla 2) en donde se clasificaron los niveles de depresión en: moderada, severa y/o grave (Arroll et al, 2010). Así como los indicadores de bienestar subjetivo: bajo y alto, para los cuales se tomó como punto de corte 13, lo que indica un mal bienestar (Espitia-Correa et al, 2020).…”
Section: Materiales Y Métodosunclassified
“…La necesidad de un instrumento que pueda brindar una valoración sobre el bienestar subjetivo llevó a desarrollar el instrumento The World Health Organisation-Five Well-Being Index (WHO-5, por sus siglas en inglés) que mide bienestar general o ausencia de síntomas depresivos, siendo un instrumento válido y confiable de acuerdo con (Espitia-Correa et al, 2020).…”
unclassified
See 1 more Smart Citation